The Influence Of Employee Branding And Organisational Citizenship Behaviour (OCB) On Employee Job Satisfaction At The Education And Culture Office Of Seluma Regency - Ayu, Hesi Putri; Anggriani , Ida; Zoniarti, Zoniarti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
There is involvement of various factors that influence employee job satisfaction, namely both factors originating from within themselves or factors related to the organizational or government environment. Both contribute to employees in positioning themselves to contribute to the organization where they work. The purpose of this study is to determine the effect of employee branding and Organizational Citizenship Behavior (OCB) together on employee job satisfaction at the Seluma Regency Education and Culture Office. The sample in this study was 81 ASN at the Seluma Regency Education and Culture Office. Data collection used a questionnaire and the analysis methods used were multiple linear regression, determination test and hypothesis test. The results of multiple regression show a positive regression direction with Y = 10.581 + 0.300X1 + 0.467 X2 +3.789. Employee branding has a significant influence on employee job satisfaction at the Seluma Regency Education and Culture Office because the significance value of 0.000 is smaller than 0.05. This illustrates that the increasing employee branding will also increase employee job satisfaction. Organizational Citizenship Behavior (OCB) has a significant influence on employee job satisfaction at the Seluma Regency Education and Culture Office because the significance value of 0.000 is smaller than 0.05. This illustrates that the higher the Organizational Citizenship Behavior (OCB), the higher the employee job satisfaction. Employee branding and Organizational Citizenship Behavior (OCB) have a significant simultaneous influence on employee job satisfaction at the Seluma Regency Education and Culture Office because the significance value of 0.000 is smaller than 0.05.